2020
DOI: 10.3389/fneur.2020.583182
|View full text |Cite
|
Sign up to set email alerts
|

Extended Study of NUS1 Gene Variants in Parkinson's Disease

Abstract: Parkinson's disease (PD), is the second most common neurodegenerative disorder worldwide. Genetic, environmental factors, and aging are its primary development contributors. Recently the nuclear undecaprenyl pyrophosphate synthase 1 homolog (Saccharomyces cerevisiae) gene (NUS1) was reported as a candidate gene for PD, which raised our interest in the relationship between NUS1 and PD. This study was aimed to further explore the role of NUS1 variants in PD development. Genetic analysis for 308 Han-Chinese PD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…NUS1 is also a proposed contributor to Parkinson’s disease (PD), as an increased frequency of missense variants within this gene have been observed in patients with early onset PD 12 ; 13 . More recent studies, however, draw this connection into question 12 ; 14 ; 15 . Other genetic studies have found de novo NUS1 variants in patients with complex dystonia, ataxia, tremor and epilepsy, reinforcing the biological importance of this gene in neuronal and/or neuromuscular systems 16 - 19 .…”
Section: Introductionmentioning
confidence: 99%
“…NUS1 is also a proposed contributor to Parkinson’s disease (PD), as an increased frequency of missense variants within this gene have been observed in patients with early onset PD 12 ; 13 . More recent studies, however, draw this connection into question 12 ; 14 ; 15 . Other genetic studies have found de novo NUS1 variants in patients with complex dystonia, ataxia, tremor and epilepsy, reinforcing the biological importance of this gene in neuronal and/or neuromuscular systems 16 - 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment of rare NUS1 variants in patients with Parkinson’s disease (PD) was described in a WES study of subjects with early-onset PD and in a second large study assessing NUS1 variants in 1542 PD cases vs 1625 controls [ 15 16 ]. However, follow-up studies, including burden analysis of rare nonsynonymous damaging variants of NUS1 in WES and WGS datasets, analysis of large PD-GWAS for rare and common variants of NUS1 , and full NUS1 sequencing in a large cohort of PD subjects failed to validate enrichment of NUS1 variants in subjects with PD [ 17 18 19 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In addition, a two‐stage screening containing 5089 patients with sporadic PD and 4423 healthy controls had found six disease NUS1 variants in PD patients 11 . Following studies in 494 and 308 sporadic Parkinson's disease patients failed to find a pathogenic variant of NUS1 in PD patients, possibly due to insufficient sample size 12,13 . Drosophila NUS1 orthologous gene tango14 protein shows 70% amino acid conservation with human NgBR in the C‐terminal cis‐IPTase domain.…”
Section: Introductionmentioning
confidence: 99%
“…11 Following studies in 494 and 308 sporadic Parkinson's disease patients failed to find a pathogenic variant of NUS1 in PD patients, possibly due to insufficient sample size. 12,13 Drosophila NUS1 orthologous gene tango14 protein shows 70% amino acid conservation with human NgBR in the C-terminal cis-IPTase domain. We knocked down tango14 in Drosophila which demonstrates phenotypes of decreased locomotion, and loss of dopaminergic neurons number and contents.…”
Section: Introductionmentioning
confidence: 99%